Metaphors Trump’s Discourse ‘Lives by’: are they Mere Pervasive Linguistic Clichés or Persuasive Tools? - Hajer, Abidi (State institute of islamic studies salatiga, 2021)
The present paper re-addresses metaphor based on Conceptual Metaphor Theory from a Critical Discourse Analysis perspective. The metaphors selected pertain to political discourse, precisely Trump’s statements on different occasions and from different sources (Twitter, YouTube). Analyzing metaphors was achieved by recourse to the identification of the source and target domains. It has been found that metaphors, albeit multi-functional persuasive tools, on so many occasions, are based on quibbles and clichéd linguistic expressions trajectories. Additionally, it has been found that metaphors acquire their effectiveness from contextual and lexical cues, in conjunction with the parameter of recipients’ knowledge. Interestingly, in some other cases, the implications of metaphors transcended the target of the speaker or writer to include some more unexpected dimensions of meaning like acquiring positive implications at the time when negative ones are anticipated, in addition to the fact that they are also a matter of feelings.Keywords: critical discourse analysis, conceptual metaphor.